A revision and standardization of the WISC verbal scale for use in Brazil - Paine, Patricia Ann; Lemgruber Garcia, Vera (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The six verbal subtests of the Wechsler Intelligence Scale for Children were revised and standardized with a sample of 640 school children ages 6 through 15. No significant differences in the mean performance of males and females were found in any subtest. Norms were established for each age level from 6 years through 15 years 1 1 months at 3 months intervals. The items of each subtest were put in a new order based on the level of difficulty. Several items of the Information and Comprehension subtests were modified and a new list of Vocabulary was adopted.